Paternal grandfather’s access to food predicts all-cause and cancer mortality in grandsons - Denny Vågerö (Nature Portfolio, 2018)
Nutritional experience can have phenotypic consequences in subsequent generations, as is evident from studies in animals and plants. Here, Vågerö et al. find in a large three-generation cohort that access to food in the paternal grandfather associates with all-cause and cancer mortality in male grandchildren.